Change of Scaling-Induced Proinflammatory Cytokine on the Clinical Efficacy of Periodontitis Treatment. (25th March 2015) - Shyu, Kou-Gi; Choy, Cheuk-Sing; Wang, Daniel Chung-Lang; Huang, Wei-Chen; Chen, Shyuan-Yow; Chen, Chien-Hsun; Lin, Che-Tong; Chang, Chao-Chien; Huang, Yung-Kai
Abstract : Proinflammatory cytokines are key inflammatory mediators in periodontitis. This study aimed to investigate the relationship between proinflammatory cytokines in saliva and periodontal status. To investigate the usefulness of cytokines in the therapeutic approach for periodontal disease, the relationship between stimulated cytokine changes and the periodontitis treatment outcome was investigated in this study. Saliva was obtained from 22 patients diagnosed by dentists as having chronic periodontitis. The proinflammatory cytokine (interleukin-1α (IL-1α ), interleukin-1β (IL-1β ), interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor α (TNF-α ), and tumor necrosis factor β (TNF-β )) levels were determined using a commercially available kit. The IL-1β and IL-6 levels increased, whereas the TNF-β levels decreased with the severity of periodontitis (4 mm pocket percentage). Poststimulation IL-1α, IL-6, and IL-8 levels were higher in patients who had an improved treatment outcome. The differences of IL-6 levels (cut point: 0.05 μ g/g) yielded a sensitivity and specificity of 90.0% and 81.82%, respectively, for predicting the periodontitis treatment outcome. Among the proinflammatory cytokines, stimulated IL-6 was an excellent marker for predicting the periodontitis treatment outcome.